Dynamic balance improvement among the elderly: Evaluating the square stepping exercise intervention - Segita, Riri; Munawarah, Siti; Olyverdi, Reza (Utan Kayu Publishing, 2025)
Dynamic balance refers to the ability to maintain postural stability during movement, which is essential for preventing falls and maintaining functional independence in elderly individuals. This study aimed to determine the effect of Square Stepping Exercise (SSE) on the dynamic balance of elderly participants. A quasi-experimental design with a one-group pretest-posttest approach was used. Ten elderly individuals were selected through purposive sampling based on specific inclusion and exclusion criteria. The Berg Balance Scale (BBS) was employed to measure dynamic balance before and after the intervention. The SSE intervention was conducted over four weeks, with three 45-minute sessions per week. Statistical analysis using paired t-tests revealed a significant improvement in dynamic balance after the intervention. The mean pretest score was 25.90 (SD = 2.76), while the mean posttest score was 28.30 (SD = 2.54), with a p-value of 0.000 (< 0.05). These results indicate that Square Stepping Exercise effectively enhances dynamic balance in elderly individuals, which may reduce the risk of falls and improve their quality of life. The findings highlight the potential of SSE as a practical, scalable intervention for fall prevention programs in elderly care settings. Abstrak: Keseimbangan dinamis mengacu pada kemampuan untuk mempertahankan stabilitas postural selama pergerakan, yang sangat penting untuk mencegah jatuh dan menjaga kemandirian fungsional pada individu lanjut usia. Penelitian ini bertujuan untuk mengetahui pengaruh Square Stepping Exercise (SSE) terhadap keseimbangan dinamis pada lansia. Desain penelitian yang digunakan adalah quasi-eksperimental dengan pendekatan pretest-posttest satu kelompok. Sepuluh lansia dipilih melalui teknik purposive sampling berdasarkan kriteria inklusi dan eksklusi tertentu. Alat ukur yang digunakan untuk menilai keseimbangan dinamis adalah Berg Balance Scale (BBS), yang diukur sebelum dan sesudah intervensi. Intervensi SSE dilakukan selama empat minggu, dengan tiga sesi per minggu, masing-masing berdurasi 45 menit. Analisis statistik menggunakan paired t-test menunjukkan peningkatan signifikan pada keseimbangan dinamis setelah intervensi. Rata-rata skor pretest adalah 25,90 (SD = 2,76), sedangkan rata-rata skor posttest adalah 28,30 (SD = 2,54), dengan nilai p sebesar 0,000 (< 0,05). Hasil ini menunjukkan bahwa Square Stepping Exercise secara efektif meningkatkan keseimbangan dinamis pada lansia, yang dapat mengurangi risiko jatuh dan meningkatkan kualitas hidup mereka. Temuan ini menegaskan potensi SSE sebagai intervensi praktis dan skala besar dalam program pencegahan jatuh di layanan perawatan lansia.